High-Speed Railways in China : A Look at Construction Costs - Ollivier, Gerald; Sondhi, Jitendra; Zhou, Nanyan (World Bank, Beijing, 2016)
By the end of 2013, China railway had built a network of about 10,000 route-km of high-speed railways (HSR). The network has been built rapidly and at a relatively low unit cost compared with similar projects in other countries. This note takes a look at this expansion, its construction unit costs and some of its key cost components. It also outlines reasons that may explain the comparatively low cost of HSR construction in China.